Padangpanjang Art Market as A Cultural Attraction and Space for Public Creativity - Fajri Wildhani Ilham; Suci Rahmadhani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study aims to analyze the role of the Padangpanjang Art Market as a cultural attraction and a platform for community creativity within the framework of developing culture-based tourism and the creative economy in Padangpanjang City. By shifting from conventional tourism paradigms to authentic experiences and the utilization of cultural heritage, the Padangpanjang Art Market has emerged as a local effort that combines art performances, culinary delights, and social interactions in an innovative public space. Using qualitative descriptive methods through literature review, in-depth interviews, field observations, and document collection, this study explores the dynamics of its organization, community participation, and the challenges encountered. Key findings indicate that the Padangpanjang Art Market boosts the local economy by increasing visits and trade activity at Padangpanjang Central Market. This weekly arts event serves as a platform for expression for artists, students, and creative groups, as well as a medium for preserving Minangkabau culture through performances of randai, traditional dance, saluang, and other arts. Participatory funding systems such as the "musician's box" demonstrate the initiative's independence, while content distribution by local content creators expands cultural promotion through digital channels. However, the study uncovered major constraints such as limited budget, manpower, and time allocation for the committee. In conclusion, Padangpanjang Art Market provides important support for strengthening cultural identity, empowering creative communities, and growing local tourism, but requires ongoing support to maintain its sustainability as an inclusive and energetic cultural space.